Development of quality improvement framework based on Japanese practices for electrical and electronics industries - Ahmad @ Mohamad, Md. Fauzi (2008)
Total Quality Management (TQM) is crucial in ensuring that a company can survive in the continuously growing competition in the global market. Japanese companies are very successful today because of adoption and implementation of TQM principles. This research studies the TQM practices between the Japanese and non- Japanese electrical and electronics companies in Malaysia. Questionnaires were prepared and sent to 370 companies and the response rate was 21.9 per cent. Analyses were made to find significant difference in TQM practices and importance between Japanese and non-Japanese companies. The results showed that there are significant differences in TQM practices. Management leadership, measurement and feedback, product design and education and training showed significant difference in favor of Japanese companies. There is no significant difference in perception on the importance of TQM except for product design. Japanese companies have high perception on the importance of product development. The top five quality activities implemented are: quality control circle, supplier improvement, Failure Mode Effect Analysis (FMEA), Value Engineering (VE) and quality costing. The main outcome of this study is a proposed Quality Improvement Guidelines (QIG) framework for TQM implementation in electrical and electronics companies in Malaysia. Management leadership, TQM awareness, standardization, customer satisfaction strategies and kaizen activities are five major parts in the framework. The framework is also supported by Critical Success Factors (CSFs) to ensure the success of TQM implementation. The framework can assist companies in meeting customer satisfaction, employee satisfaction and business growth.